Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Van Mullem, P. (International Journal of Sports Science & Coaching, 2018)
Simon Jenkins interview with Dr. Andy Gillham provides key insight into the role of a coach consultant in coach development and coach education in the United States. The term coaching consultant describes an individual that works directly with coaches to improve coaching practice.2 A coaching consultant may share in the role of educating coaches with sport psychologists, coaching educators (i.e. faculty in higher education), coach developers (i.e. National Governing Bodies), and sport researchers (i.e. coaching scientists). Dr. Gillham. a trained sport psychologist, operates mainly in the role of coaching consultant. Although as the interview highlights. Gillham has demonstrated the ability to fulfill multiple roles in building his credibility as an educator of coaches. For the purpose of this commentary, the term coaching consultant will refer to all professionals working with or engaged in the process of educating coaches.